Macro- and Micronutrient Simultaneous Slow Release from Highly Swellable Nanocomposite Hydrogels - Bortolin, Adriel; Serafim, Andre R.; Aouada, Fauze A. [UNESP]; Mattoso, Luiz H. C.; Ribeiro, Caue (Amer Chemical Soc, 2016)
Clay-loaded hydrogels have been arousing great interest from researchers and, academics due to their unique properties and broad applicability range. Here we developed hydrogel-based nanocomposites intended for slow/controlled release of macro- and micronutrients into independent or concurrent systems. The produced nanocomposites underwent a hydrolysis treatment that improved their physicochemical properties. We obtained materials capable of absorbing water contents 5000 times greater than their weights, an outcome that makes them promising, particularly if compared with commercially available materials. Though swelling degree was affected by the presence of calcium montmorillonite (MMt), MMt has increased nutrient (urea and boron) loading capacity and, as a consequence of its interaction with the studied nutrients, has led to a slower release behavior. By evaluating the simultaneous release behavior, we observed that both the ionic (sodium octaborate) and the nonionic (urea) sources competed for the same active sites within the nanocomposites as suggested by the decreased loading and release values of both nutrients when administrated simultaneously. Because of its great swelling degree, higher than 2000 times in water, the nanocomposites formulated with high MMt contents (approximately 50.0% wt) as well as featuring high loading capacity and individual (approximately 74.2 g of urea g(-1) of nanocomposite and 7.29 g of boron g(-1) of nanocomposite) and simultaneous release denote interesting materials for agricultural applications (e.g., carriers for nutrient release).
Keywords: swelling degree; hydrolysis; nanocomposite; nanoclay; simultaneous release